Analisis Hukum Interrnasional Terhadap Allowable Catch Dalam Upaya Pencegahan Praktik Overfishing dan Penerapannya di Indonesia - Zunit, Jemie Devano; Zora, Zimtya (UI Scholars Hub, 2023)
The sea has a huge amount of potential. With an abundance of fish and very wonderful biodiversity. However, nowadays there are many irresponsible individuals who overexploit the biological riches in the sea, resulting in overfishing. Overfishing is a method of excessive fishing which will have an impact on a drastic and continuous decline in fish populations which will later lead to extinction. For this reason, we need a way to suppress overfishing, namely the implementation of allowable catch. Allowable catch can be used by coastal states as a management technique to limit fishing in certain areas. This study used normative juridical research methods with descriptive research specifications and analyzed them through library research. Allowable catch has been regulated in international law on Article 61 of UNCLOS 1982 with the hope of reducing overfishing rates. To determine the allowable catch, use the formula JTB = 80% x MSY. The implementation of allowable catch in Indonesia has been regulated in the Ministerial Decree of Maritime Affairs and Fisheries Republic of Indonesia Number 19 of 2022 concerning Estimation of Fish Resource Potential, JTB, and the Level of Fish Resource Utilization in the Fisheries Management Areas of the Republic of Indonesia. In this Ministerial Decree, the level of utilization has been divided into 3 categories, namely moderate (in the developing stage), fully-exploited (saturated or close to saturation), and overfishing (excessive fishing).